Hot melt extruded-based nano zinc as an alternative to the pharmacological dose of ZnO in weanling piglets - Oh, Seung Min (Asian-Australasian journal of animal sciences, 2020)
OBJECTIVE: This study was conducted to investigate the effects of hot-melt extruded ZnO nano-particles (HME-ZnO) as an alternative for P-ZnO on growth performance, nutrient digestibility, Zn bioavailability, intestinal microbiota, and intestinal morphology of weanling pigs